Positive Cognitive Triad- a link between Self Efficacy and Resilience, Prosocial behavior and Hostility - Nidhi (Thapar university, 2022)
ABSTRACT The research examined into the impact of the newly arising concept Positive Cognitive Triad in mediating the relationship between psychological dimensions including self-efficacy and pro-social behaviour, resilience, and hostility levels in adolescents. To see how one's positive cognitive processes associates with their self-esteem and, in addition, other characteristics. The findings from 166 Children suggest a significant positive link between cognitive triad and self efficacy (r =.40, p < 0.01), as well as a positive correlation between positive cognitive triad and resilience (r =.212, p < 0.05). The positive cognitive triad appears to have an important role in mediating the relationship between self-efficacy and resilience. However, there was no evidence of a its link between Prosocial conduct and hostility. Furthermore, regression analysis also revealed that the Cognitive triad accounted for 17% of the variance in self efficacy.
NA
Keywords: Positive Cognitive Triad; Hostility; Pro-social Behaviour; Self efficacy; Resilience; Adolescents; Variance